'He can do whatever he wants': a pregnant teens' reflections on leisure and a romantic relationship. Issue 5 (20th October 2021) - Clark, Brianna S.; Walters, Kellie A.; Anderson, Denise M.; Mims, Sarah
ABSTRACT: Romantic relationships and leisure play significant roles in adolescents' lives. However, heterosexual romantic relationships can negatively constrain women's leisure, particularly with regard to 'shared' leisure among heterosexual couples impacted by pregnancy. While some attention has been given to the leisure experiences of pregnant girls, the constraining influence of romantic relationships compounded by pregnancy on a young girls' leisure remains unexplored. Therefore, this exploratory study aimed to describe pregnant adolescents' leisure within heterosexual relationships. Findings are presented as fictional blog passages and text message exchanges over the course of the composite, Opal's pregnancy. This fictional representation describes how Opal's leisure not only changed but diminished as a result of pregnancy, yet her boyfriend's leisure remained nearly unchanged.